Urgensi Pembatasan Periodisasi Anggota Lembaga Perwakilan Rakyat Dalam Sistem Ketatanegaraan Indonesia - Aulia, Pandhit Jauharlal Nehru Sultan; Saputra, Dadin Eka; Ridho, M. Rosyid (Media Hukum Indonesia (MHI), 2025)
Judging from the continuation of leadership that exceeds the period limit determined by the Constitution, this can lead to the risk of arbitrary power and criminal acts of corruption occurring, because power continues to be maintained.The aim of this research is specifically aimed at answering two things. First, this research aims to determine the legal implications of not limiting the periodization of members of the People's Representative Council in the Indonesian constitutional system. Second, to identify and find appropriate forms of legal regulation in limiting the periodization of members of the House of Representatives.The research method used is normative juridical with a statutory regulatory approach, also known as library legal research.The results of this research indicate that the legal implications of not limiting the periodization of members of people's representative institutions in the Indonesian constitutional system, namely, the mandate or guarantee of the right to obtain equal opportunities in government as a constitutional mandate is not implemented, degrades the meaning of people's representation in the Indonesian constitutional system, and does not realize appropriate treatment. universal and balanced between legislative candidates, and the existence of political dynasties within the body of the people's representative institutions which will become an important problem and threaten the country, and there will be a tendency towards static thinking which will hinder the nation's progress.